Development of Green Chemistry Oriented Student Worksheets with Guided Inquiry Model to Improve Science Literacy Skills on Reaction Rate Material - Pratiwi, Karina Rike; Mitarlis, Mitarlis (Jurnal Pijar Mipa, 2025)
Green chemistry plays a crucial role in minimizing the environmental impact of chemical processes, while science literacy equips students with the knowledge and skills to understand a sustainable future. This study aims to describe the feasibility of a Student Worksheet oriented toward green chemistry using a guided inquiry model, deemed suitable for enhancing students’ scientific literacy skills in the reaction rate topic. The research method employed is the Research and Development (R&D) 4D model, which includes define, design, develop, and disseminate stages, limited in this study to the development stage to analyse needs, design, and test the conformity of the learning media. A limited trial was conducted with 30 eleventh-grade students who had previously received instruction on reaction rate and green chemistry at a senior high school in Nganjuk during the 2024/2025 academic year. Data were collected through questionnaires, observations, and tests, then analyzed quantitatively and descriptively using mode, percentage, Guttman scale, Likert scale, and N-Gain test. The results show that the worksheet is valid in terms of content and construct (mode 4, good category), practical based on student responses (97.5%, very good), student activities (96.86%, very good), and implementation (mode 5, very good). The worksheet was also effective in improving scientific literacy, as evidenced by 90% of students achieving a gain score ≥ 0.7 (high category). N-Gain by indicator: context 0.85, knowledge 0.85, and competence 0.88. Based on its validity, practicality, and effectiveness, the developed worksheet is feasible to use as a learning medium.